The Influence of Fiqh Thaharah Practices and Consistency in Performing Dhuha Prayer on the Morals of Seventh-Grade Students at Darul Hijroh Canden Islamic Junior High School Boarding School, Academic Year 2025/2026 - Yahya Hizbu Rohim; Ngatmin Abbas; Rara Intan Mutiara Fajrin (Darul Yasin Al Sys, 2026)
Students’ moral development in Islamic educational settings is closely related to the habituation of worship practices, including fiqh thaharah and consistency in performing dhuha prayer. This study aims to examine the influence of fiqh thaharah practices and dhuha prayer consistency on the moral character of seventh-grade students at MTs Pondok Pesantren Darul Hijroh Canden during the 2025/2026 academic year. A quantitative field research approach with an ex post facto correlational design was employed. Data were collected through questionnaires, observation, and documentation using a saturated sampling technique. Data analysis involved descriptive and inferential statistics through multiple linear regression, supported by validity, reliability, and classical assumption tests. The findings indicate that fiqh thaharah practices and consistency in performing dhuha prayer positively and significantly influence students’ moral character, both partially and simultaneously. Students with stronger worship habituation tended to demonstrate better discipline, responsibility, and moral awareness. The study concludes that structured worship habituation contributes to strengthening students’ moral development in Islamic educational institutions. This study contributes to Islamic education and character education by providing empirical evidence on the role of religious practice habituation in shaping students’ moral character. The practical implication is that Islamic educational institutions should design systematic, consistent, and supervised worship habituation programmes to support sustainable character formation among students.